Phosphorylated thiacalixarenes as molecular receptors for QCM sensors of volatile compounds - Kazantseva, Z.I.; Koshets, I.A.; Belyaev, A.E.; Ryabitskii, A.B.; Kharchenko, S.G.; Drapailo, A.B.; Kalchenko, V.I.; Shishkina, S.V.; Shishkin, O.V. (Functional Materials, 2017)
Sorption of volatile organic compounds and ammonia by thin solid films of phosphorylated thiacalixarenes was investigated by the quartz crystal microbalance (QCM), X-ray crystallography and molecular modeling methods The interfacial sorption depends on the number and position (upper or lower rim) of P=O groups on the macrocyclic skeleton, the electronic nature of the substituents at the phosphorus atom. At low concentrations of the analytes their sorption occurs according to the Langmuir isotherm due to specific supramolecular interactions with receptor centers of the thiacalixarenes. The analytes may form either the Host-Guest inclusion complexes stabilized by C-H...π interactions, or extracavity complexes stabilized by hydrogen bonds with oxygen atoms of the peripheral P=O groups. At high concentrations, when the thiacalixarene receptor centers are occupied by the analytes, further sorption occurs nonspecifically according to the linear Henry isotherm due to inclusion of the analytes in voids of the crystal structure of the thiacalixarenes.